THE IMPORTANCE OF CORPORATE BRANDS FOR DECISION MAKING IN THE BUSINESS-TO-BUSINESS CONTEXT - Nikolina Koporčić; Zdravko Tolušić; Zlatko Rešetar (Ekonomski Vjesnik, 2017)
The purpose of this paper is to provide a deeper understanding of the importance of the corporate brand for the business-to-business (B2B) context, specifically concerning the buyer and supplier decision-making processes. The paper provides a literature review on tangible and intangible brand attributes, as well as their influence on perceived risks and emotions in decision making. The findings imply that business decision making is not solely rational, and that emotions matter a great deal. The conceptual framework thus presents the process of business decision making in which brand attributes play a focal role for both the buyer and supplier. Research implications include three aspects: the importance of corporate brands and their attributes for reducing a buyer´s perceived risks when choosing a new supplier, the role of corporate brands for strategies that suppliers are using when attracting potential buyers, and the effect of emotions on the mentioned processes. The paper offers a new comprehensive framework for studying decision-making in the B2B context and contributes to corporate branding and decision-making theory development.